Studi Variabilitas Produktivitas Primer Bersih di Perairan Selatan Indonesia Berdasarkan Data Satelit Aqua Modis - Ni Nyoman Raka Wulandari; Ni Luh Novita Aryanti; I Gede Hendrawan (Department of Marine Sciences, Faculty of Marine Science and Fisheries, Udayana University, 2019)
The Indonesian waters have special characteristics which are influenced by its existence between the two continents and two oceans. The placement between two continents and oceans resulted in highly dynamic oceanographic conditions, one of them being primary productivity. Net primary productivity in a water body is strongly influenced by the presence of nutrient, light, chlorophyll-a, Photosynthetically Active Radiation (PAR) and sea surface temperature (SST). The purpose of this research is to find out the net primary productivity variability in the south Indonesian waters based on Aqua-MODIS. The data used in this research are obtained using satellite data and a VGMP model (a vertically Generalized Production Model) is used to analyse the net primary productivity. One of the satellite images can be used to estimate the net primary productivity in the waters is MODIS (Moderate Resolution Imaging Spectroradiometer) sensor, with specifications of level 3 with a resolution of 4 km. The results obtained of net primary productivity value in the southern waters of Indonesia showed 150 mgC m2 day -1 - 200 mgC m2 day -1, with the highest peak being in November 2006 and the lowest in September 2010. The highest value of net primary productivity is caused due to upwelling waters events found.